Talleres para desarrollar la autonomía en los niños de primer año de preparatoria - Chiguano Ante, Ana Lucia (2022)
Based on the diagnosis established by Calero and Sigsi (2022) on the Pedagogical Model "The Social Cognitive Pedagogical Model in the development of the autonomy of the children of the First Year of High School", which was developed in the Educational Unit "San José de Guaytacama ” the lack of knowledge that exists about the application of the Social Cognitive Model in the development of the autonomy of the children of the First Year of High School during the Teaching-Learning Process is evident, for this reason it was found that the teachers use different methodologies in their classroom work like that of Montessori, Froebel, Pestalozzi, among others. It was carried out with the qualitative and quantitative approach process, because it used data collection techniques such as interview, survey and observation sheet with their respective instruments, the same ones that facilitate obtaining the necessary information. In order to respond to the detected problem, the general objective is proposed "Design workshops for the development of autonomy in first-year high school children of the "San José de Guaytacama" Educational Unit in the 2021-2022 school year", therefore Therefore, 8 workshops were developed to promote and develop autonomy, which are described in the proposal "CLIMBING THE TREE OF AUTONOMY". The workshops carried out are based on the constructivist approach where constructivism is conceived as a process through which children are helped, supported, and directed in the construction of their own knowledge, this arises as the child learns new things. such as drawing, debating and writing, is important because it allows you to develop the autonomy of your cognitive skills as a human being, developing the emotional and social aspect; with the acquisition of habits, skills and practice of values. The validations of the workshops were reviewed and qualified by expert fourth-level teachers, licensed users who are from Initial Education, who concluded that the playful workshops are suitable for application inside and outside the institutions. Determining that the development of autonomy is fundamental in children, especially at an early age, therefore, they will be independent children where they carry out their activities without the help of an adult and forming self-confident adolescents, favoring their critical and moral thinking.